TryMeOut: A Vulnerability Web Application for Security Students Learning - Abdullah, Muhammad Muaazin; Mohamad Sukri, Khairul Amin (Applied Information Technology And Computer Science, 2025)
TryMeOut is a web-based platform developed to support cybersecurity students in gaining practical, hands-on experience with common web application vulnerabilities. This platform allows students to safely explore and exploit real-world vulnerabilities such as SQL injection, Cross-Site Scripting (XSS), and Command Injection in a secure, controlled environment. The system features a progression of interactive challenges, starting from basic scenarios and advancing to more complex ones. This structure helps students build their skills gradually, reinforcing core concepts while encouraging exploration and problem-solving. Each vulnerability category includes multiple levels that simulate realistic attacks, giving students valuable experience in recognizing, exploiting, and understanding the impacts of these threats. Targeted primarily at bachelor’s degree students in the Information Security program at Universiti Tun Hussein Onn Malaysia (UTHM), the platform aims to offer a user-friendly, educational space that bridges the gap between theory and real-world application. This project is developed using the Waterfall Model methodology, which follows a clear, linear process from planning and analysis to design, implementation and testing.